Pembuatan Video Pariwisata Sebagai Sarana Promosi Dan Pengenalan Wisata Yang Ada Di Kota Bengkulu - Ahmad Abdul Maliq; M Ari Adriansyah; Defpry Pramana; Chessar Safari; Khairullah Khairullah (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2022)
Promotion can be interpreted as an effort or communication tool to introduce a product from a particular company so that it can be known to the public and attract buyers so as to increase company sales. In this study, several work implementation activities were presented, findings of obstacles or problems and proposed solutions to obstacles or problems encountered at the Bengkulu City Tourism Office for 1 month, namely January 24 2022 to February 26 2022. The City Tourism Office is the tourism manager -tours in the city of Bengkulu. During the Omicron pandemic, the tourism office could not carry out events aimed at introducing tourism to the city of Bengkulu. Therefore the Bengkulu City Tourism Office wants to make a tourism promotion video in the city of Bengkulu. It is hoped that by making a tourism promotion video, people in Bengkulu province and outside Bengkulu province can find out about it.